The Islamic Sharia Approach in the Prevention of Contemporary Mental Illness: An Analytical Study - Muneer Ali Abdul Rab; Mahmoud Mohamed Ali Mahmoud Edris; Baidar Mohammed Mohammed Hasan; Setiyawan Gunardi; Lutfi Muhammad Zain; Mesbahul Hoque (Usuli Faqih Research Centre PLT, 2024)
Indexed by MyCite